(3eNJUQ efM GdcfhR heaGJjM GdQehRs - (3TQa GdOjf CHhYHO Gddg eMeO Hf YKeGf Hf Ydj GdCfUGQj YQa HGHf Hf CHi SYjOs; (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s ((3eMeO Hf eMeO GdHdjGfi s)
(3ChdgG (B:s
(3GeG HYO gPg GdLedI GdLGeYI dTJGJ eG JaQb ai GdYGde TQbkG hZQHkG s
(3BNQgG (B:s
(3eYGfi GSeGFg Edi BNQg (B357 (3eQI HYO UdGI hPcQ hWgGQg s
(3Vef eLehY , JQJjHgG (B: (3GdKGfi YTQs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B698s
Keywords: (3GdMQha h GdChaGbs